The Right Man for the Job - Pieter A. Gautier (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper describes a search model with a continuum of workerand job types, transferable utility and an increasing returns to scale contact technology. We apply a second order Taylor expansion to characterize the equilibrium. One third of theincreasing returns in contacts are absorbed by firms and workers being more choosy. Hence, strongly increasing returns in contact rates are consistent with weakly increasing returns in matching. The resulting equilibrium is not efficient. Unemployment benefitscan reduce the loss by serving as a search subsidy. The loss caused by search frictions is higher when worker types are bad substitutes. Numerical simulations of the model show our Taylor expansions to be quite accurate.
Keywords: 330; assignment; search; unemployment